Biologie a ekologie ohroženého druhu Liparis loeselii (L.) Rich. z čeledi Orchidaceae a generativní množení metodou in vitro - Pavlová, Jana (Jihočeská univerzita, 2007)
Biologie a ekologie ohroženého druhu Liparis loeselii (L.) Rich. z čeledi Orchidaceae a generativní množení metodou in vitro
Biology and ecology of endangered species Liparis loeselii (l.) from Family orchidaceae and generative Propagation using in vitro method
Keywords: Orchidaceae; Liparis loeselii; in vitro metody; Orchidaceae; Liparis loeselii; in vitro methods